Controllable ALD synthesis of platinum nanoparticles by tuning different synthesis parameters. (15th September 2017) - Wang, Chuandao; Hu, Linhua; Lin, Yuyuan; Poeppelmeier, Kenneth; Stair, Peter; Marks, Laurence
Abstract: Pt nanoparticles were successfully deposited using three different atomic layer deposition (ALD) methods, e.g. AB-type, ABC-type and static ABC-type ALD, on two different types of strontium titanate nanocuboids (STO-NCs) samples in a reaction temperature window of 125 °C–300 °C. The influence of reaction temperature, number of ALD cycles, type of substrate, 2nd reagent and type of ALD method on Pt nanoparticle deposition are comprehensively studied and discussed in this work. Varying the reaction temperature and number of cycles across the three different ALD methods affects Pt particle size, density, and loading. Surface termination of STO-NCs substrate will change deposited Pt nanoparticle growth orientation and thermodynamic shape. The B reagent besides platinum precursor can lead to different ligand decomposition mechanism when Pt precursors are exposed: oxygen allows more effective ligand combustion compared to water, however, the Pt particles are more oxidized according to XPS studies. We expect this work provides a way for tailoring nanoparticles with desired size, dispersion, exposed surfaces and chemical state etc, which helps controlling and optimizing their performance when applied as catalysts or nanosensors.